Two new records of Lasianthus (Rubiaceae) for the Flora of Laos - Pham , Q. T.; Tagane, S.; Souladeth, P.; Yamamoto, T.; Phonepaseuth, P.; Vongthavone, T.; Kongxaisavath, D.; Truong, B. V.; Dang, V. S. (Rheedea, 2025)
Two species of Lasianthus Jack (Rubiaceae), viz. L. biflorus (Blume) M.Gangop. & Chakrab. and L. hispidulus (Drake) Pit., from Nam Kading National Protected Area in central Laos, are reported as new records for the Flora of Laos. Taxonomic description, habitat, distribution, voucher specimens, and color photographs are provided for each species.